Serum- and glucocorticoid-inducible kinase 1 and the response to cell stress - Florian Lang; Christos Stournaras; Nefeli Zacharopoulou; Jakob Voelkl; Ioana Alesutan (Cell Stress, 2018)
Expression of the serum- and glucocorticoid-inducible kinase 1 (SGK1) is up-regulated by several types of cell stress, such as ischemia, radiation and hyperosmotic shock. The SGK1 protein is activated by a signaling cascade involving phosphatidylinositide-3-kinase (PI3K), 3-phosphoinositide-dependent kinase 1 (PDK1) and mammalian target of rapamycin (mTOR). SGK1 up-regulates Na+/K+-ATPase, a variety of carriers including Na+-,K+-,2Cl–– cotransporter (NKCC), NaCl cotransporter (NCC), Na+/H+ exchangers, diverse amino acid transporters and several glucose carriers such as Na+-coupled glucose transporter SGLT1. SGK1 further up-regulates a large number of ion channels including epithelial Na+ channel ENaC, voltage-gated Na+ channel SCN5A, Ca2+ release-activated Ca2+ channel (ORAI1) with its stimulator STIM1, epithelial Ca2+ channels TRPV5 and TRPV6 and diverse K+ channels. Furthermore, SGK1 influences transcription factors such as nuclear factor kappa-B (NF-κB), p53 tumor suppressor protein, cAMP responsive element-binding protein (CREB), activator protein-1 (AP-1) and forkhead box O3 protein (FOXO3a). Thus, SGK1 supports cellular glucose uptake and glycolysis, angiogenesis, cell survival, cell migration, and wound healing. Presumably as last line of defense against tissue injury, SGK1 fosters tissue fibrosis and tissue calcification replacing energy consuming cells.